Sound Scattering Layers Within and Beyond the Seychelles-Chagos Thermocline Ridge in the Southwest Indian Ocean - Kang, Myounghee; Kang, Jung-Hoon; Kim, Minju; Nam, SungHyun; Choi, Yeon; Kang, Dong-Jin (Frontiers in Marine Science, 2021)
In global oceans, ubiquitous and persistent sound scattering layers are frequently detected with echosounders. The southwest Indian Ocean has a unique feature, a region of significant upwelling known as the Seychelles-Chagos Thermocline Ridge (SCTR), which affects sea surface temperature and marine ecosystems. Despite their importance, sound scattering layers within and beyond the SCTR are poorly understood. This study aimed to compare the characteristics of the sound scattering layers within and beyond the SCTR in connection with environmental properties, and dominant zooplankton. To this end, the region north of the 12°S latitude in the survey area was defined as SCTR, and the region south of 12 °S was defined as non-SCTR. The results indicated contrasting oceanographic properties based on the depth layers between SCTR and non-SCTR regions. Distribution dynamics of the sound-scattering layers differed between the two regions. In particular, the diel vertical migration pattern, acoustic scattering values, metrics, and positional properties of acoustic scatterers showed two distinct features. In addition, the density of zooplankton sampled was higher in SCTR than in the non-SCTR region. This is the first study to present bioacoustic and hydrographic water properties within and beyond the SCTR in the southwest Indian Ocean.